GREEN INNOVATION, FINANCIAL PERFORMANCE, AND FIRM VALUE: A CONTENT ANALYSIS METHOD - Emi Lestari; Hardi Bahar (Value : Jurnal Manajemen dan Akuntansi, 2023)
A rapid increase in environmental concerns has prompted firms to engage in green innovation. This study aimed to analyze and synthesize theories that explain the effect of green innovation and financial performance on increasing firm value and financial performance on increasing firm value. This study uses a qualitative approach with the literature review method, which is an approach that examines and synthesizes previous research by selecting relevant literature, conducting analysis and mapping and interpreting literature synthesis. This study examines 25 articles from Google Scholar, Mendeley Search, Emerald insight and Harzing’s Publish or Pherish. This study maps the theoretical basis, other explanatory variables and research results from the previous literature. The underlying theories include the signaling theory and legitimacy theory. The synthesis of the research results shows three types of research results. The first is research which explains that green innovation has a significant positive effect on increasing firm value. Second is the research group which explains that green innovation has a significant positive effect on increasing firm value. The third is the research group which explains that financial performance significantly affects increasing firm value. The contribution of this research provides a conceptual framework that provides direction for future research. Keywords: green innovation, financial performance, and firm value